Remote sensing of sea ice properties and dynamics using SAR interferometry - Marbouti, Marjan (Helsingin yliopisto, 2022)
Landfast ice is attached to the coastline and islands and stays immobile over most of the ice season. It is an important element of polar ecosystems and plays a vital role as a marine habitat and in life of local people and economy through offshore technology. Landfast ice is routinely used for on-ice traffic, tourism, and industry, and it protects coasts from storms in winter from erosion. However, landfast ice can break or experience deformation in order of centimeters to meters, which can be dangerous for the coastline and man-made structures, beacons, on-ice trafﬁc, and represents a safety risk for working on the ice and local people. Therefore, landfast ice deformation and stability are important topics in coastal engineering and sea ice modeling. In the framework of this dissertation, InSAR (SAR Interferometry) technology has been applied for deriving landfast ice displacements (publication I), and mapping sea ice morphology, topography and its temporal change (publication III). Also, advantages of InSAR remote sensing in sea ice classification compared to backscatter intensity were demonstrated (publications II and IV). In publication I, for the first time, Sentinel-1 repeat-pass InSAR data acquired over the landfast ice areas were used to study the landfast ice displacements in the Gulf of Bothnia. An InSAR pair with a temporal baseline of 12 days acquired in February 2015 was used. In the study, the surface of landfast ice was stable enough to preserve coherence over the 12-day period, enabling analysis of the interferogram. The advantage of this long temporal baseline is in separating the landfast ice from drift ice and detecting long-term trends in deformation maps. The interferogram showed displacements of landfast ice on the order of 40 cm. The main factor seemed to be compression by drift ice, which was driven against the landfast ice boundary by strong winds from southwest. Landfast ice ridges can hinder ship navigation, but grounded ridges help to stabilize the ice cover. In publication III, ...